(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
A graph is called total cordial if it has a labeling such that the total number of vertices and edges labelled with ones and zeros differ by at most one. In this paper, we contribute some new results on Total Product cordial labeling and investigate necessary and sufficient conditions of the corona product between paths and second power of fan graphs to be total cordial